Working memory capacity in a go/no-go task: Age differences in interference, processing speed, and attentional control. - Rodríguez Villagra, Odir Antonio (2013)
We tested the limits of working-memory capacity (WMC) of young adults, old adults, and children with a memory-updating task. The task consisted of mentally shifting spatial positions within a grid according to arrows, their color signaling either only go (control) or go/no-go conditions. The interference model (IM) of Oberauer and Kliegl (2006) was simultaneously fitted to the data of all groups. In addition to the 3 main model parameters (feature overlap, noise, and processing rate), we estimated the time for switching between go and no-go steps as a new model parameter. In this study, we examined the IM parameters across the life span. The IM parameter estimates show that (a) conditions were not different in interference by feature overlap and interference by confusion; (b) switching costs time; (c) young adults and children were less susceptible than old adults to interference due to feature overlap; (d) noise was highest for children, followed by old and young adults; (e) old adults differed from children and young adults in lower processing rate; and (f) children and old adults had a larger switch cost between go steps and no-go steps. Thus, the results of this study indicated that across age, the IM parameters contribute distinctively for explaining the limits of WMC.